Fabricación heroica y construcción de la memoria histórica chilena (1844-1875) - Jean Pierre Dedieu; Lucrecia Enríquez; Gabriel Cid Rodríguez (Caravelle, 2015)
This article deals with the construction of memory in nineteenth century Chile through «hero making». We analize a gender seldom studied: galleries of famous men appearing in printed versions. Even though they were composed by different authors, there is a link between them, which enables us to postulate that they were a priviliged means for this heroic making.